Effective conservation of melanistic lizard species in the Greater Cederberg Biodiversity Corridor - Janse van Rensburg, Dahne A. (Stellenbosch : University Stellenbosch, 2010)
Thesis (PhD (Zoology))--University of Stellenbosch, 2009.